Information experiences of young generation social media users in Indonesia’s political year 2024 - Hanifatunnisa, Najwa Auliana; Lusiana, Elnovani; Perdana, Fitri (Universitas Padjadjaran, 2025)
Background: As future leaders of the nation, the young generation's task is to comprehend the complexity of the various issues that arise in society, including those related to politics. On the other hand, their innate status as digital natives also affect the way they process information. The unstoppable dynamics of information in the online world create a variety of experiences for them. Purpose: This study aimed to determine the information experience of young social media users throughout the 2024 political year in Indonesia. Methods: The research method used was qualitative. Data were obtained from observation activities and interviews with seven informants. The informants were selected based on several criteria to ensure their experiences were relevant to this study. The collected research data were analyzed thematically, resulting in four themes: lifestyle, information packaging, social media assessment, and information sharing. Results: Study results showed that lifestyle was related to gadget usage, daily political information access, and K-pop. Information packaging included short duration, audio-visual content, independence, humor, and textual aspects. Social media assessment highlights Twitter as a platform capable of training and enhancing intellectuality. Information sharing forms sub-themes such as education, self-expression, reciprocity, and hoaxes. Conclusion: This study concludes that the political information experience of the younger generation today is closely integrated with their lifestyle, information packaging, social media assesment, and information sharing activity. Implications: These results suggest that the information disseminators recommended creating content to increase audience engagement. Social media platforms can be used to cultivate digital literacy and facilitate discussions. However, these findings also emphasize the urgency of strengthening information filters to mitigate the negative impact of information-sharing patterns that risk spreading hoaxes.